How do Different Management Strategies (Standard Phototherapy, Intensive Phototherapy, and Pharmacological Interventions) to Neonatal Jaundice ? : A Systematic Review - Putu Ardy Hartadi; Komang Vika Nariswari Ratna Kinasih; Wayan Suwidja Haryasa (The International Journal of Medical Science and Health Research, 2025)
Introduction: Neonatal jaundice is a common condition that requires effective management to prevent neurotoxic outcomes like kernicterus. While conventional phototherapy is the standard treatment, numerous advanced strategies have been developed to improve efficacy. This systematic review evaluates the comparative effectiveness of different management strategies, including intensive phototherapy, varying phototherapy modalities, and pharmacological interventions, to guide clinical practice. Methods: This review followed the PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed, Springer, Semantic Scholar, Google Scholar, and Wiley Online Library for randomized controlled trials, systematic reviews, and prospective cohort studies published since 2014. The search focused on interventions such as intensive phototherapy and pharmacological adjuncts compared to standard phototherapy in neonates with jaundice. Key outcomes included bilirubin reduction, treatment duration, and adverse effects. After screening 281 records, 20 studies were included for data synthesis. Results: The 20 included studies showed that intensive and double-surface phototherapy significantly accelerate bilirubin reduction and shorten treatment duration compared to conventional methods. LED phototherapy demonstrated superior or comparable efficacy with fewer side effects than fluorescent lamps. Adjunctive therapies, including zinc, clofibrate, and Clostridium butyricum, consistently reduced bilirubin levels and therapy duration. Low-cost innovations like filtered sunlight and reflective curtains were found to be effective alternatives in resource-limited settings. Conclusion: Numerous advanced and adjunctive therapies are more effective than conventional phototherapy for neonatal jaundice. The evidence supports a tailored approach, selecting interventions like intensive phototherapy, LED technology, and pharmacological adjuncts based on clinical severity and resource availability. This allows for optimized, safer, and more efficient management of neonatal hyperbilirubinemia.